ChemInform Abstract: Catalytic Asymmetric exo‐Selective [6 + 3] Cycloaddition of Iminoesters with Fulvenes. Issue 2 (14th January 2014) - Potowski, Marco; Antonchick, Andrey P.; Waldmann, Herbert
Abstract The title reaction proceeds with high diastereo‐ and enantioselectivity and allows the selective formation of piperidine derivatives.